Pengaruh Pemberian Core Stability Dan Swiss Ball Exercise Terhadap Skala Nyeri Pada Pasien Spondylosis Lumbal Di Rumah Sakit Umum Mitra Medika Tanjung Mulia Medan - Surya Syahputra Berampu (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
Background: Lumbar spondylosis is a degenerative condition that occurs in the bodies and lumbar intervertebral discs which is characterized by the formation of osteophytes in the inferior and superior bodies of the lumbar vertebrae. This condition is called lumbar spondylosis which causes pain, decreased muscle flexibility and limited range of motion. Core Stability and Swiss Ball Exercise are methods that are implemented for this pathologist. Purpose: To determine the effect of Core Stability and Swiss Ball Exercise on pain scale in Lumbar Spondylosis sufferers. Methods: This research is a Quasi-Experimental study with a one group pre test and post test design design to see the effect of Core Stability and Swiss Ball Exercise on pain scale in Lumbar Spondylosis sufferers. Results: The normality test of the Shapiro wilk test obtained a sig. VAS before physiotherapy was 0.063 and sig. VAS after physiotherapy 0.069 > 0.05 then H0 is accepted and Ha is rejected, which means the data distribution is normal. Hypothesis testing using the Paired Sample T-test obtained results for the Sig VAS value. 2 tailed for a VAS value of 0.00 <0.05, H0 is accepted and Ha is rejected, indicating that there is an effect of Core Stability and Swiss Ball Exercise on reducing the pain scale in Lumbar Spondylosis sufferers. Conclusion: There is an effect of Core Stability and Swiss Ball Exercise on reducing pain scale in patients with lumbar spondylosis at Mitra Medika Hospital Tanjung Mulia Medan.